1999
DOI: 10.1126/science.285.5426.418
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Vertebrate Sister-Chromatid Separation Inhibitor Involved in Transformation and Tumorigenesis

Abstract: A vertebrate securin (vSecurin) was identified on the basis of its biochemical analogy to the Pds1p protein of budding yeast and the Cut2p protein of fission yeast. The vSecurin protein bound to a vertebrate homolog of yeast separins Esp1p and Cut1p and was degraded by proteolysis mediated by an anaphase-promoting complex in a manner dependent on a destruction motif. Furthermore, expression of a stable Xenopus securin mutant protein blocked sister-chromatid separation but did not block the embryonic cell cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
600
0
11

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 743 publications
(621 citation statements)
references
References 25 publications
8
600
0
11
Order By: Relevance
“…Although we cannot discard that these sites could be phosphorylated at low level by Cdc2, our S 165 A mutant almost completely abrogated the in vitro phosphorylation by this kinase, indicating that this optimal consensus site is the main phosphorylation site. Interestingly this serine is conserved in rat and mouse PTTG, however it is not present in the Xenopus PTTG sequence (Zou et al, 1999). The possibility that the phosphorylation of other serine in Xenopus have the same role that phosphorylation of Ser 165 in human PTTG, needs further investigation.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Although we cannot discard that these sites could be phosphorylated at low level by Cdc2, our S 165 A mutant almost completely abrogated the in vitro phosphorylation by this kinase, indicating that this optimal consensus site is the main phosphorylation site. Interestingly this serine is conserved in rat and mouse PTTG, however it is not present in the Xenopus PTTG sequence (Zou et al, 1999). The possibility that the phosphorylation of other serine in Xenopus have the same role that phosphorylation of Ser 165 in human PTTG, needs further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…These observations further raise the possibility that hpttg may be involved in regulating progression through the cell cycle and, more speci®cally, through the M phase. During the revision of this manuscript, Zou et al (1999) reported that PTTG encodes a securin, a protein which inhibits sister-chromatid separation by binding to separin. Our results are in total agreement with this function of hPTTG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At anaphase the ubiquitin-ligase anaphase-promoting complex (APC) induces the degradation of Securin, an inhibitor of the protease Separase, which in turn cleaves the Rad21 subunit of cohesin [42][43][44]. Sister chromatids are now free to follow the pull of the mitotic spindles and to segregate towards the newly forming daughter cells.…”
Section: The Cohesin Complexmentioning
confidence: 99%